Discovery and Characterization of Novel BLIMP‑1 Heterobifunctional Ligand-Directed Degraders - Bryan J. Simmons (22676881) (2025)
B-lymphocyte-induced maturation protein 1 (BLIMP-1/PRDM1) is a master transcriptional repressor essential for terminal differentiation of activated B-cells into bone-marrow resident plasma cells. Multiple myeloma (MM) is a plasma cell malignancy wherein the BLIMP-1 regulon remains critical to support basal cell functions, such as an elevated metabolic state and immunoglobulin production that underlie disease manifestation and tumor cell proliferation. It is predicted that perturbation of BLIMP-1 will significantly impact tumor cell homeostasis and ultimately reduce MM cell survival. Herein, we describe the discovery and optimization of the first orally bioavailable BLIMP-1 heterobifunctional ligand-directed degrader (LDD) and demonstration of the expected antitumor response and immunomodulatory biology following BLIMP-1 degradation using preclinical in vivo MM models.